2016
DOI: 10.1039/c5ta09662f
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric properties of CH3NH3PbI3perovskite thin films and their applications in piezoelectric generators

Abstract: CH3NH3PbI3(MAPbI3) perovskite thin films were applied for piezoelectric generators under various applied pressures, poling field conditions, and switching polarity test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
125
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 22 publications
7
125
0
Order By: Relevance
“…the domain structure that typifies a ferroelectric material are found to be quite contradictory (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). To analyze the question whether HaPs are actually ferroelectric, we need to test for the presence/absence of several fundamental phenomena that are tightly related to it.…”
Section: Significancementioning
confidence: 99%
“…the domain structure that typifies a ferroelectric material are found to be quite contradictory (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). To analyze the question whether HaPs are actually ferroelectric, we need to test for the presence/absence of several fundamental phenomena that are tightly related to it.…”
Section: Significancementioning
confidence: 99%
“…For example, the piezoelectric coefficient decreased by replacing I with Cl or Br because the covalent bond strength between Pb and X is reduced . A typical piezoelectric energy generator and its working mechanism are described in Figure …”
Section: Applications Beyond Photovoltaicsmentioning
confidence: 99%
“…[2][3][4] However, whether or not OMH perovskites are ferroelectric materials or exhibit other ferroic properties, and which effects might result from these properties have been a subject of debate for several years. Claims included piezoelectricity, [15][16][17] pyroelectricity, [5] ferroelasticity, [9,12,18] antiferroelectricity [19] as well as ferroelectricity, [10,11,15,16,20] and the seemingly contradictory reports on these ferroic properties have heated up the discussion. Scanning microscopy techniques such as atomic force microscopy (AFM), [9][10][11][12] scanning electron microscopy (SEM), [13] and tunneling electron microscopy (TEM) [14] were extensively used in order to reveal the microstructure of OMH-perovskite thinfilm samples with subgrain resolution.…”
mentioning
confidence: 99%
“…A multitude of measurement techniques was employed in order to probe ferroic properties of single crystal samples, [5,6] pressed powder pellets, [7] and polycrystalline thin-films [8] of OMH perovskites. Claims included piezoelectricity, [15][16][17] pyroelectricity, [5] ferroelasticity, [9,12,18] antiferroelectricity [19] as well as ferroelectricity, [10,11,15,16,20] and the seemingly contradictory reports on these ferroic properties have heated up the discussion. Some of these studies revealed ordered domains within crystal grains, but no consensus has been reached about the interpretation of their ferroic and crystallographic origins.…”
mentioning
confidence: 99%